Long-term comparative effectiveness and safety of dabigatran, rivaroxaban, apixaban and edoxaban in patients with atrial fibrillation: A nationwide cohort study - Grymonprez, Maxim; De Backer, Tine L.; Bertels, Xander; Steurbaut, Stephane; Lahousse, Lies (Frontiers in Pharmacology, 2023)
Background: Although non-vitamin K antagonist oral anticoagulants (NOACs) are recommended over vitamin K antagonists (VKAs) in atrial fibrillation (AF) management, direct long-term head-to-head comparisons are lacking. Therefore, their risk-benefit profiles were investigated compared to VKAs and between NOACs. Methods: AF patients initiating anticoagulation between 2013-2019 were identified in Belgian nationwide data. Inverse probability of treatment weighted Cox regression was used to investigate effectiveness and safety outcomes and were additionally stratified by NOAC dose. Results: Among 254,478 AF patients (328,796 person-years of follow-up), NOACs were associated with significantly lower risks of stroke or systemic embolism (stroke/SE) (hazard ratio (HR) 0.68, 95% confidence interval (CI) (0.64-0.72)), all-cause mortality (HR 0.76, 95%CI (0.74-0.79)), major or clinically relevant non-major bleeding (MB/CRNMB) (HR 0.94, 95%CI (0.91-0.98)) and intracranial hemorrhage (HR 0.73, 95%CI (0.66-0.79)), but non-significantly different risks of myocardial infarction, gastrointestinal and urogenital bleeding compared to VKAs. Despite similar stroke/SE risks, dabigatran and apixaban were associated with significantly lower MB/CRNMB risks compared to rivaroxaban (HR 0.86, 95%CI (0.83-0.90); HR 0.86, 95%CI (0.83-0.89), respectively) and edoxaban (HR 0.91, 95%CI (0.83-0.99); HR 0.86, 95%CI (0.81-0.91), respectively), and apixaban with significantly lower major bleeding risks compared to dabigatran (HR 0.86, 95%CI (0.80-0.92)) and edoxaban (HR 0.79, 95%CI (0.72-0.86)). However, higher mortality risks were observed in some risk groups including with apixaban in patients with diabetes or concomitantly using digoxin compared to dabigatran and edoxaban, respectively. Conclusion: NOACs had better long-term risk-benefit profiles than VKAs. While effectiveness was comparable, apixaban was overall associated with a more favorable safety profile followed by dabigatran.